Dictionary, lexicon, glossary, wordbook or thesaurus? The usefulness of OALDCE7 and OLT for choosing the right word - Dziemianko, Anna (Afûk, 2010)
The aim of the present study is to investigate the usefulness of the Oxford Advanced Learner’s Dictionary of Current English (7th edition, OALDCE7) and the Oxford Learner’s Thesaurus (OLT) for discriminating between synonyms. The paper is underpinned by empirical research, in which 73 advanced learners of English took part. In the experiment, words appropriate for given contexts had to be indicated in different synonym sets. The results reveal that neither dictionary significantly shortened the time needed to complete the task. Nonetheless, the use of OLT much more often resulted in successful synonym selection. Interestingly, synonym notes, present in both dictionaries, did not affect the subjects’ choices. Besides, different information was usually referred to in the two dictionaries. In OALDCE7 the subjects paid attention most often to definitions, while in OLT – to examples. The results of the supplementary questionnaire suggest that the students’ familiarity with the two dictionary types could not have affected their performance. They were nonetheless more satisfied with their results when they had OLT at their disposal rather than OALDCE7. Yet, they were critical of the arrangement of synonyms in the OLT synonym clusters, where the alphabetical order, rather than frequency, would be a better solution.